Penggunaan Sapaan dalam Keluarga pada Masyarakat Aceh Utara - Misna Misna; Khalsiah Khalsiah; Maulidawati Maulidawati (FKIP Universitas Palangka Raya, 2026)
This study aims to describe the forms and usage of terms of address within family interactions in the North Aceh community, as well as to identify the factors influencing their use. The research was conducted in Gampong Meunasah Meucat and several surrounding villages in North Aceh Regency. The research employed a descriptive qualitative method, with data collected through observation, semi-structured interviews, and documentation. The data were obtained from direct utterances of native speakers of the Acehnese language who understand and use kinship-based address systems in daily interactions. The findings reveal that the family address system in the North Aceh community can be categorized into two types, namely those based on lineage and marital relationships. Based on lineage, 31 forms of address were identified, such as Ama, Ayah, and Apak to refer to biological fathers. Based on marital relationships, 18 forms of address were identified, such as Temude and Abang to address the husband of an older sister. The use of these address terms is influenced by social and situational factors, including age, social status, level of familiarity, and cultural or regional background. This study concludes that the family address system in the North Aceh community is highly rich and complex, reflecting values of respect and kinship that are strongly upheld within the community. To preserve this linguistic tradition, awareness among younger generations is essential, along with support from the government and educational institutions through the integration of language-related materials into the curriculum and cultural preservation programs.